2017
DOI: 10.1021/acs.energyfuels.6b02659
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Kinetic Insights into the Octane Number and Octane Sensitivity of Gasoline Surrogate Mixtures

Abstract: Gasoline octane number is a significant empirical parameter for the optimization and development of internal combustion engines capable of resisting knock. Although extensive databases and blending rules to estimate the octane numbers of mixtures have been developed and the effects of molecular structure on autoignition properties are somewhat understood, a comprehensive theoretical chemistry-based foundation for blending effects of fuels on engine operations is still to be developed. In this study, we present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
76
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 71 publications
11
76
0
Order By: Relevance
“…The highest regression coefficient (R 2~0 .8, adjusted R 2~0 .79) between known RON values and calculated IDT was obtained for T=750K and P=40 bar. The T-P values were similar to those suggested in previous literature [4,27]. The endgas ahead of the flame front was compressed and heated; this T-P was representative of the endgas before auto-ignition.…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…The highest regression coefficient (R 2~0 .8, adjusted R 2~0 .79) between known RON values and calculated IDT was obtained for T=750K and P=40 bar. The T-P values were similar to those suggested in previous literature [4,27]. The endgas ahead of the flame front was compressed and heated; this T-P was representative of the endgas before auto-ignition.…”
Section: Methodssupporting
confidence: 87%
“…Sarathy et al proposed that the RON of PRFs can be correlated with IDT calculated at po of 20 atm and To of 835 K [26]. Badra et al further expanded the correlation for toluene reference fuel (TRF), and toluene primary reference fuels (TPRF) [27] with po of 50 atm and To of 850 K. Singh et al utilized up to six components for their formulation, correlating RON and IDT with high regression, at po of 25 bar To of 750 K [4]. Westbrook et al used experimentally obtained pressure data to find ignition delay times corresponding to RON and MON values of pure and compound mixtures [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Simulated hydroxyl time-history profiles during the oxidation of stoichiometric mixtures of the three surrogates (PRF 60, TPRF 60, and MCS) are presented in Fig. 7 at 20 bar and 650 K. Previous studies by Merchant et al [46] and others [41,47,48] have shown that OH radical profiles provide insights into the chemical kinetics of ignition processes. The initial growth of OH radicals is similar between all the fuels, but at ~5 ms the OH radical growth for MCS slows compared to that of PRF and TPRF.…”
Section: Low-temperatures Chemical Kinetic Analysismentioning
confidence: 96%
“…Sensitivity analysis also shows that the heat release and OH concentration are sensitive to the isomerization of cyclopentyl peroxy radical (CPTO2J) to QOOH radical (CPT1Q3J). Our previous studies on cyclopentane oxidation [49,50] and mixtures comprising cyclopentane [41,47] have explained its ignition characteristics. Furthermore, hydroxyl (OH) and hydroperoxyl (HO2) rate-of-production analyses were performed for the multi-component surrogate, Fig.…”
Section: Low-temperatures Chemical Kinetic Analysismentioning
confidence: 99%
“…Complex low-temperature termination, propagation, and branching pathways forming alkenes, cyclic ethers, and ketohydroperoxides (KHP) [9,10], respectively, control heat release rate, raise system temperature, and advance formation and decomposition of H2O2. The chemical kinetics of low-temperature oxidation [11] is strongly related to fuel molecular structure, and can be linked to interesting combustion phenomena such as cool flames [12], negative temperature coefficient (NTC) behavior [13], and fuel anti-knock quality (i.e., octane numbers) [14].…”
Section: Introductionmentioning
confidence: 99%